EVALUATING THE IMPACT OF GOVERNMENT POLICY ON MATERNAL HEALTH: A STUDY OF PRADHAN MANTRI MATRU VANDANA YOJANA IN DAKSHIN BIDYANAGAR VILLAGE OF HOJAI DISTRICT, ASSAM - Singha, Mahima; Hazarika, Barnali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Pradhan Mantri Matru Vandana Yojana (PMMVY) is a flagship maternity benefit program launched by the Government of India in 2017. Its primary objective is to provide financial assistance to pregnant and lactating women, aiming to improve their overall health and nutritional status. This initiative plays a pivotal role in enhancing maternal health and promoting the well-being of both mothers and newborns across India. Despite the program's potential, several factors influence the accessibility and utilization of PMMVY benefits. Understanding these determinants is crucial for maximizing the scheme's reach among eligible beneficiaries. Variables such as age, education, awareness, the application process, and socioeconomic conditions are key in determining how effectively the program's benefits are accessed. Each of these factors can either facilitate or obstruct the successful implementation of PMMVY. The study tries to examines the effect of the independent variables like age, education, and awareness on the benefits of PMMVY scheme. It also explores the potential association between PMMVY beneficiaries and their preferred place of delivery. Additionally, the paper analyzes obstacles in availing PMMVY benefits and proposes measures to overcome these challenges.